Acute effects of strength exercises and effects of regular strength training on cell free DNA concentrations in blood plasma - Tug, S.; Tross, A. K.; Hegen, P.; Neuberger, E. W. I.; Helmig, S.; Schöllhorn, W.; Simon, P. (PLOS ONE, 2017)
Creatine kinase (CK) is a marker for muscle cell damage with limited potential as marker for training load in strength training. Recent exercise studies identified cell free DNA (cfDNA) as a marker for aseptic inflammation and cell damage. Here we overserved in a pilot study the acute effects during strength exercise and chronic effects of regular strength training on cfDNA concentrations over a period of four weeks in three training groups applying conservation training (CT) at 60% of the 1 repetition maximum, high intensity-low repetition training (HT) at 90% of the 1 repetition maximum and differential training (DT) at 60% of the 1 repetition maximum. EDTA-plasma samples were collected before every training session, and on the first and last training day repeatedly after every set of exercises. CfDNA increased significantly by 1.62-fold (mean (±SD) before first exercise: 8.31 (2.84) ng/ml, after last exercise 13.48 (4.12) ng/ml) across all groups within a single training session (p<0.001). The increase was 1.77-fold higher (mean (±SD) before first exercise: 12.23 (6.29) ng/ml, after last exercise 17.73 (11.24) ng/ml) in HT compared to CT (mean (±SD) before first exercise: 6.79 (1.28) ng/ml, after last exercise 10.05 (2.89) ng/ml) (p = 0.01). DNA size analysis suggested predominant release of short, mononucleosomal DNA-fragments in the acute exercise setting, while we detected an increase of mostly longer, polynucleosomal cfDNA-fragments at rest before the training session only at day two with a subsequent return to baseline (p<0.001). In contrast, training procedures did not cause any alterations in CK. Our results suggest that during strength exercise short-fragmented cfDNA is released, reflecting a fast, aseptic inflammatory response, while elevation of longer fragments at baseline on day two seemed to reflect mild cellular damage due to a novel training regime. We critically discuss the implications of our findings for future evaluations of cfDNA as a marker for training load in strength training.